A short C-terminal sequence is necessary and sufficient for the targeting of chitinases to the plant vacuole - Neuhaus, Jean-Marc; Sticher, L.; Meins, F. Jr.; Boller, T. (My University, 1991)
Tobacco contains different isoforms of chitinase (EC 3.2.1.14), a hydrolase thought to be involved in the defense against pathogens. Deduced amino acid sequences for putatively vacuolar, basic chitinases differ from the homologous extracellular, acidic isoforms by the presence of a C-terminal extension. To examine the role of this C-terminal extension in protein sorting, Nicotiana silvestris plants were stably transformed with chimeric genes coding for tobacco basic chitinase A with and without the seven C-terminal amino acids. In plants expressing unmodified chitinase A, the enzyme activity was low in the intercellular wash fluid but high in protoplasts and isolated vacuoles. In contrast, in plants expressing mutant chitinase lacking the C terminus, the activity was high in the intercellular wash fluid but low in protoplasts. N. silvestris plants were also transformed with similar constructions coding for a structurally unrelated, extracellular cucumber chitinase. In plants expressing unmodified cucumber chitinase, its activity was present in the intercellular wash fluid and absent from protoplasts. In plants expressing cucumber chitinase with the C-terminal extension from tobacco chitinase A, activity was low in intercellular wash fluids but high in protoplasts and vacuoles. These results demonstrate that the C-terminal extension of tobacco chitinase A is necessary and sufficient for the vacuolar localization of chitinases and, therefore, that it comprises a targeting signal for plant vacuoles.
Keywords: Amino Acid Sequence; Base Sequence; Chitinase/*genetics/metabolism; DNA/genetics; Immunoblotting; Isoenzymes/*genetics/metabolism; Molecular Sequence Data; Mutagenesis; Site-Directed; Oligodeoxyribonucleotides; *Plants; Toxic; Plasmids; Protoplasts/enzymology; Tobacco/*enzymology/genetics; Vacuoles/*enzymology